Physiological responses and growth of Samanea saman grown in a biodegradable seedling container filled with post-silica mined soil media in the greenhouse - Sri Wilarso Budi; Andi Sukendro; Cahyo Wibowo; Khiorunnisa Rizki Dwi Jayati (Journal of Degraded and Mining Lands Management, 2023)
A biodegradable seedling container was developed to minimize plastic waste in the field during post-mining land revegetation activities. Therefore, this study aims to evaluate the physiological response and growth of Samanea saman grown in a biodegradable seedling container filled with post-silica mined soil media. A factorial experimental design was used with two factors, namely (1) basic raw materials, namely recycled newspaper, compost, and cocopeat, and (2) size of raw materials, including 5 mesh, 10 mesh, and 8 mesh. The parameters measured were photosynthetic rate, leaf greenness index, transpiration rate, height, and diameter of S. saman seedlings. The results showed that the interaction between the composition and size of basic raw materials of the biodegradable seedling container significantly increased the photosynthetic rate, leaf greenness index, transpiration rate, height, and diameter of seedlings. There was also a positive correlation between the rate of photosynthetic and leaf greenness index (r = 0.838). Furthermore, the C/N ratio of the biodegradable pot varied depending on the composition of materials used. After two months, the C/N ratio decreased, indicating that decomposition processes had occurred. Analysis of the biodegradable seedling container showed that it contains less than 0.08 mg Pb kg-1, which was considered a non-toxic element for plant growth.